Access to Green. Enhancing Urban. Attractiveness in Urban Centers – the Case of Turku. - Jones, Ana Maria; Wilenius, Markku; Niskanen, Suvi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2019)
Our experience of life on Earth is shaped by our environment. As development continues to grow increasingly urban, access to green areas continue to become central to human health and to ensure quality of life. The integrated design of green areas in planning is a multi-dimensional and cross-disciplinary process that requires a combination of approaches namely, a network design approach, functionality, scalability, and sustainability management approach to help cities and communities deal with the unprecedented challenges of the century. This study calls attention to the need for more quality, access and adequate distribution of green areas in urban cores. Focusing on the city center districts of the city of Turku, this report addresses the need for more development in the design and holistic planning of green areas as providers of human health and attractive urban life. The study emphasizes the critical need to carry out a more detailed inventory of green areas and current access requirements.